Strategi Pembelajaran PAKEM - Alimiddin, Akhyar; U, Usman; Shabir U, M. (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The implementation of PAKEM in various educational institutions faces various challenges. Among them are teachers' limited understanding of the comprehensive concept and practice of PAKEM, as well as resistance to changes in more interactive teaching methods. In addition, facilities and infrastructure that support active learning are still inadequate in many schools, especially in remote areas. This hinders the full implementation of PAKEM and causes inequality in the quality of education received by students. In addition, although PAKEM is recognized as effective in increasing student engagement and deepening their understanding of the subject matter, many still question its effectiveness in improving long-term academic outcomes. Other factors such as more complex classroom management and the need for training and support for teachers to implement PAKEM effectively are also challenges. In this study, the author used a qualitative descriptive method with the main data source from library data. Furthermore, the data was coded, reduced, and conclusions were drawn. The results of the study show that the PAKEM learning strategy (Active, Creative, Effective, and Enjoyable Learning) offers an innovative approach that aims to increase student engagement in the learning process. By encouraging students to actively participate, think creatively, and experience enjoyable learning experiences, PAKEM is able to create a more dynamic and meaningful educational environment. Although this strategy faces challenges, such as the need for longer preparation time and complex classroom management, the benefits are far greater.